Tandem termination signal in plant mRNAs - Kochetov, Alex V. (2011)
It was proposed that if some mRNA characteristics resulted in a low efficiency of termination signal, an additional closely located stop codon (tandem stop codons) could be used to prevent the harmful readthrough. However, the role of tandem terminators in higher eukaryotes was not verified and remains hypothetical. In this work the sequence features of Arabidopsis thaliana and Oryza sativa mRNAs were analyzed. It was found that plant mRNAs with UGA terminator were characterized by a higher frequency of nonsense codons in the first triplet position of 3′-UTR that could result from a weak natural selection for “reserve” stop signal. Interestingly, the presence of tandem stop codons positively correlated with a specific amino acid composition in the C-terminal position of the encoded proteins. In particular, C-terminal glycine positively correlated with significantly higher frequencies of reserve terminators at the beginning positions of 3′-UTR in UGA-containing mRNAs. This finding coincides with some earlier observations concerning the role of glycine and its codons in inefficient termination of translation and recoding (e.g., 2A oligopeptide).